2022
DOI: 10.1021/acs.jafc.2c01867
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PxαE14 Contributing to Detoxification of Multiple Insecticides in Plutella xylostella (L.)

Abstract: The diamondback moth, Plutella xylostella (L.), has evolved with varying degrees of resistance to almost all major classes of insecticides and has become the most resistant pest worldwide. The multiresistance to different types of insecticides has been frequently reported in P. xylostella, but little is known about the mechanism. In this study, a carboxylesterase (CarE) gene, PxαE14, was found significantly overexpressed in a field-evolved multiresistant P. xylostella population and can be dramatically induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…More recently, the constitutive and inductive overexpressions of several α-esterases were selected by using forward and reverse genetic approaches in multi-insecticide resistant Plutella xylostella strains [ 102 ]. Further functional studies suggested that the overexpression of one of these esterases, Px αE14, may play roles in resistance to multiple OP and pyrethroid insecticides in P. xylostella [ 103 ].…”
Section: Dynamic Rules Of Insect Cces In Chemical Adaptationmentioning
confidence: 99%
“…More recently, the constitutive and inductive overexpressions of several α-esterases were selected by using forward and reverse genetic approaches in multi-insecticide resistant Plutella xylostella strains [ 102 ]. Further functional studies suggested that the overexpression of one of these esterases, Px αE14, may play roles in resistance to multiple OP and pyrethroid insecticides in P. xylostella [ 103 ].…”
Section: Dynamic Rules Of Insect Cces In Chemical Adaptationmentioning
confidence: 99%
“…Shi et al (2016) showed that the esterase TCE2 of T. cinnabarinus (Boisduval) was able to degrade the pyrethroid fenpropathrin [ 104 ], while, very recently, it was also shown that an esterase of the fungus gnat, Bradysia odoriphaga , had significant hydrolase activity towards the ester-containing substances bifenthrin and malathion [ 105 ]. Lastly, Li et al reported that two esterases of Plutella xylostella (Pxα14 and PxEST-6) could metabolize bifenthrin and that the RNAi knockdown of Pxα14 caused an increase in resistance to bifenthrin [ 106 , 107 ]. Based on these examples, we selected two CCEs—CCE58, overexpressed in all pairwise comparisons, and CCEinc18, overexpressed in four pairwise differential gene expression analyses—as the top candidates to study their bifenthrin-metabolizing potential.…”
Section: Discussionmentioning
confidence: 99%
“…To better protect humans and livestock from the harmful effects of pesticides, it is urgently needed to develop effective analytical methods, especially those that can target mixed pesticides [ 11 ]. So far, malathion, phoxim, and thiram in agricultural products can be accurately measured using high-performance liquid chromatography (HPLC) [ 12 ], gas chromatography tandem mass spectrometry (GC-MS) [ 13 ], and liquid chromatography tandem mass spectrometry (LC-MS) [ 14 ]. However, these techniques require sophisticated and expensive instruments, as well as fully-trained technicians, to operate.…”
Section: Introductionmentioning
confidence: 99%